1976
DOI: 10.1002/jcp.1040890311
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal hydrolase secretion by Tetrahymena: A comparison of several intralysosomal enzymes with the isoenzymes released into the medium

Abstract: Tetrahymena pyriformis were grown in proteose-peptone medium and then washed and incubated in a dilute salt solution for one hour. The cells were then discarded and the lysosomal hydrolases that had been secreted were subjected to DEAE cellulose column chromatography. At least three isoenzymes of acid phosphatase, three of acid protease, and two of beta-N-acetylhexoseaminidase were found, as well as single peaks of alpha-mannosidase, beta-galactosidase, and beta-fucosidase. The latter two activities were not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…Dickie and Liener [4] have isolated two different extracellular proteases with neutral pH optimum and one intracellular acid protease having the optimum at pH 5.5 for denatured hemoglobin. Miiller [2] noted the release of an acid protease having pH optimum at 3.3 for denatured hemoglobin and Blum [32] suggested that two or more acid proteases hydrolyzing denatured hemoglobin at pH 3.3 were secreted into the medium. Furthermore, extensive studies have been performed by Levy and coworkers [ll], who isolated several isoenzyme forms of intracellular protease possessing a neutral optimum pH for synthetic substrate and azocasein and an optimum of pH 3.3 for denatured hemoglobin.…”
Section: Optimum P Hmentioning
confidence: 99%
“…Dickie and Liener [4] have isolated two different extracellular proteases with neutral pH optimum and one intracellular acid protease having the optimum at pH 5.5 for denatured hemoglobin. Miiller [2] noted the release of an acid protease having pH optimum at 3.3 for denatured hemoglobin and Blum [32] suggested that two or more acid proteases hydrolyzing denatured hemoglobin at pH 3.3 were secreted into the medium. Furthermore, extensive studies have been performed by Levy and coworkers [ll], who isolated several isoenzyme forms of intracellular protease possessing a neutral optimum pH for synthetic substrate and azocasein and an optimum of pH 3.3 for denatured hemoglobin.…”
Section: Optimum P Hmentioning
confidence: 99%
“…Recently, interest has been shown in the role of cysteine proteases in the pathology of parasitic infections. These proteases can be released from the parasites (Blum, 1976;Keene, 1986; Lockwood et al, 1988; Garber and Lemchuk-Favel, 1989;North et al, 1989; Boutignon et al, 1990) andmay beinvolved in the pathology of the diseases and the survival of the parasites within the host (Bremmer et al …”
mentioning
confidence: 99%
“…Because the content and the composition of the lysosomal enzymes secreted by T. thermophila are strongly media-dependent, 62,63 the portfolio of the different N-linked glycans in T. thermophila might be influenced by the prevailing cultivation conditions. It remains to be determined if the observed range of N-glycan structures is the result of incomplete processing during intracellular transport, whether it is dependent on the resident time in the extracellular medium, or if it is the result of a normal variation.…”
Section: Discussionmentioning
confidence: 99%